UPAYA PENINGKATAN MINAT BACA MATERI PENDIDIKAN AGAMA ISLAM MELALUI PROGRAM LITERASI SEKOLAH DI SMP UNGGULAN USWATUN HASANAH CILEGON - Nurhayati, Is; Firdaus, Ahmad (THORIQOTUNA: Jurnal Pendidikan Islam, 2020)
Efforts to increase interest in reading Islamic religious education materials through school literacy programs are very important for an educational process of students in the current era of globalization. With the interest in reading students can broaden broad knowledge, such as general knowledge, religion and others and with reading interest activities can also be carried out together with the school literacy program.This process can also foster students' character with reading activities because of the tendency of students towards these activities. The method used is descriptive qualitative method, research This uses purposive sampling, research steps with data collection techniques with interviews. The conclusion obtained in this study is based on the results of the author's research on "Efforts to Increase Interest in Reading Islamic Education Materials" that, Based on this it can be seen the level of interest in reading Islamic religious education materials through the school literacy program at Uswatun Hasanah SMPU greatly increased by performing stages as well as the steps and efforts of teachers in fostering a fondness for reading students at school so that the formation of attitudes that can instill confidence to read critically and be ready to face future challenges.